1998
DOI: 10.1097/00001756-199812210-00005
|View full text |Cite
|
Sign up to set email alerts
|

APE/Ref-1 responses to ischemia in rat brain

Abstract: Cerebral ischemia and the aftermath of reperfusion form a hypoxic/hyperoxic sequence of events that can trigger oxidative stress response cascades in neurons of the central nervous system. After transient ischemia there is an increase in intracellular Ca2+ release, extracellular glutamate, reactive oxygen species (ROS) and nitric oxide, genotoxic events that stimulate DNA repair. Increased oxidative stress and interrupted blood flow in ischemia, like DNA repair, also deplete cellular ATP and commit neurons to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 7 publications
2
24
0
Order By: Relevance
“…It appears that the cell uses p53 to downregulate APE1 expression in response to DNA damage, and promotes apoptosis. Consistent with this idea, several earlier studies showed reduction of APE1 expression during apoptosis in neurons after transient global cerebral ischemia in rats (34,50,90,143). Additional studies are needed to unravel the physiological significance of such downregulation.…”
Section: Regulation Of Ape1 Expressionmentioning
confidence: 52%
See 1 more Smart Citation
“…It appears that the cell uses p53 to downregulate APE1 expression in response to DNA damage, and promotes apoptosis. Consistent with this idea, several earlier studies showed reduction of APE1 expression during apoptosis in neurons after transient global cerebral ischemia in rats (34,50,90,143). Additional studies are needed to unravel the physiological significance of such downregulation.…”
Section: Regulation Of Ape1 Expressionmentioning
confidence: 52%
“…Isobaric hyperoxia (100% oxygen) stimulated APE1 expression in the hippocampus and basal forebrain of young rats, while aged rats showed no significant changes in APE1 protein levels in all brain areas after hyperoxia (35,118). In contrast, several studies showed that global cerebral ischemia or traumatic brain injury or cold injury-induced brain trauma (100) induced oxidative stress decreases APE1 expression in the hippocampus and is associated with neuronal apoptosis in rats (34,50,143). This specific inhibition of APE1 expression may affect the extent of apoptosis after ischemia.…”
Section: Ape1 In Neurodegenerative and Cardiovascular Diseasesmentioning
confidence: 99%
“…The early rapid reduction of APE is also seen in vulnerable hippocampal CA 1 neurons in rodents after transient global cerebral ischemia (Edwards et al, 1998;Kawase et al, 1999a). The rapid reduction of APE appears to be sensitive to oxidative stress because overexpression of CuZnSOD in SOD1 mice prevents the early reduction of APE in the ischemic brain (Fujimura et al, 1999c).…”
Section: P H Chanmentioning
confidence: 99%
“…For example, studies have shown that APE1 expression is lowered by ischemia before cell death (14,21,24,29,34). APE1 levels decrease after both transient cerebral ischemia (24,29) and traumatic brain injury (35), generally preceding DNA fragmentation.…”
Section: Ape1 Preserves Neuronal Structure and Functionmentioning
confidence: 99%